Indonesia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
The corporate sector in Indonesia has been recovering in recent years from the financial crisis of 1997-98. This paper analyzes the performance of the Indonesian nonfinancial corporate sector in recent years and discusses remaining challenges and vulnerabilities. The decline in corporate leverage may have resulted to a large extent from supply-side constraints. Indonesia was the country most severely affected by the Asian financial crisis, with GDP declining by 13 percent in 1998. Despite modest bank intermediation, bank financing has regained prominence as a source of corporate financing in recent years.